Ginsenoside Rg1 inhibits proliferation of vascular smooth muscle cells stimulated by tumor necrosis factor-α - Ma Zeng-chun; Gao Yue; Wang Yu-guang; Tan Hong-ling; Xiao Cheng-rong; Wang Sheng-qi (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the proliferation of vascular smooth muscle cells (VSMC) affected by ginsenoside Rg1 and further explore the molecular mechanism of ginsenoside Rg1 using proteomics. Methods: The proliferation of VSMC was measured by MTS assay kit and flow cytometry. Proteomic alterations were analyzed using two-dimensional electrophoresis and peptide mass fingerprinting. Differential proteins found in proteomics were confirmed by RT-PCR. Results: The proliferation of VSMC was enhanced significantly after tumor necrosis factor-α (TNF-α) treatment, and ginsenoside Rg1 treatment inhibited proliferation in a dose-dependent manner. Proteomic analysis showed 24 protein spots were changed, including 17 spots that were increased and 7 spots that were decreased. Ginsenoside Rg1 could restore the expression levels of these proteins, at least partly, to basic levels of untreated cells. The expression of G-protein coupled receptor kinase, protein kinase C (PKC)-ζ, N-ras protein were decreased, while cycle related protein p21 was increased by ginsenoside Rg1 in TNF-α treated VSMC. Conclusion: PKC-ζ and p21 pathway might be the mechanism for inhibitory effects of ginsenoside Rg1 on proliferation of VSMC.